regions. peripheries and centres - Grigoryeva, Elena (project baikal, 2023)
This year, the spring is full of events. In April the winners of the open architectural competition for the reconstruction of the D.A. Hvorostovsky Krasnoyarsk State Opera and Ballet Theatre were announced (16). The annual meeting of the Russian Academy of Architecture and Construction Sciences was held in Moscow (7-15). The program article of academician Dmitry Shvidkovsky contains many serious thoughts about the role of the architect in the context of these difficult times, among which is one that sounds particularly relevant for historic cities (to which Irkutsk has the honour to belong): it is vitally important both for the urban planning community and the representatives of corresponding branches of government to seek to form an absolutely respectful, interested or at least tolerant attitude to the national heritage in order to strengthen patriotism and the sense of homeland among Russian citizens. Traditional spaces and building types need to be preserved and restored where possible (8). The topical exhibition “Restoration of Destroyed Cities” is described by its ideologist and author, academician Dmitry Bush (12). The main theme of the issue is devoted to the regions and the changing relationship between centres and peripheries. In this millennium, the network model of world perception begins to develop rapidly, so in the Discussion Club moderated by Konstantin Lidin we talk about the multidimensional space in which there are many centres and, consequently, many peripheries. Thus, the notion of the centre becomes relative: any place can be called a centre if we find a suitable plane with a suitable network to match it. The theoretical articles of our regular contributors discuss the development of traditional notions of centre and periphery, of the ‘heart’ of a city, of national architecture. Specific examples of settlements in Arctic Russia and old Kursk are used to explore the new meanings that make these places centres of attention.